CryoEM Reveals the Complexity and Diversity of ATP Synthases - Courbon, Gautier M.; Rubinstein, John L. (Frontiers in Microbiology, 2022)
During respiration, adenosine triphosphate (ATP) synthases harness the electrochemical proton motive force (PMF) generated by the electron transport chain (ETC) to synthesize ATP. These macromolecular machines operate by a remarkable rotary catalytic mechanism that couples transmembrane proton translocation to rotation of a rotor subcomplex, and rotation to ATP synthesis. Initially, x-ray crystallography, nuclear magnetic resonance (NMR) spectroscopy, and cross-linking were the only ways to gain insights into the three-dimensional (3D) structures of ATP synthases and, in particular, provided ground-breaking insights into the soluble parts of the complex that explained the catalytic mechanism by which rotation is coupled to ATP synthesis. In contrast, early electron microscopy was limited to studying the overall shape of the assembly. However, advances in electron cryomicroscopy (cryoEM) have allowed determination of high-resolution structures, including the membrane regions of ATP synthases. These studies revealed the high-resolution structures of the remaining ATP synthase subunits and showed how these subunits work together in the intact macromolecular machine. CryoEM continues to uncover the diversity of ATP synthase structures across species and has begun to show how ATP synthases can be targeted by therapies to treat human diseases.